Using Independent Learning Log for Listening Skill Learning Among First Year University Students - Salimah, Salimah; Dewanti, Anna (Journal of English Education Program, 2024)
Students freshly admitted to the English Language and Literature study program has various levels of English proficiency. To maximize their listening skills, independent learning log was administered to the students to support their learning activities outside classroom. This action research was aimed at investigating the benefits of the log for the students"™ listening skills, and for the students"™ English learning in general. Data was collected from a listening class comprising 42 students. Each student was given an independent learning log and had to complete the log outside the classroom. Classroom discussions during the log completion were carried out in several meetings throughout the semester. In addition, the independent learning reflection was conducted at the last week of the semester. The findings indicate that the benefits of using the independent learning log for students were self-paced learning, more personalized choices, and more peer collaboration. Specifically, students became more self-directed and autonomous. Furthermore, they shared learning resources, forming a class-based learning community. Collectively, all of these benefit their future learning.